2019
DOI: 10.1021/acs.chemmater.8b04734
|View full text |Cite
|
Sign up to set email alerts
|

Active Role of Methanol in Post-Synthetic Linker Exchange in the Metal–Organic Framework UiO-66

Abstract: UiO-66 is known as one of the most robust metal-organic framework materials. Nevertheless, UiO-66 has also been shown to undergo post-synthetic exchange of structural linkers with surprising ease in some solvents. To date, the exchange mechanism has not yet been fully elucidated. Here, we show how timeresolved monitoring grants insight into the selected case of exchanging 2-aminoterephthalate into UiO-66 in methanol. Analysis of both the solid and liquid phase, complemented by computational insights, revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 52 publications
7
65
0
Order By: Relevance
“…During this process, possibly EtOH/EtO − pairs replaced formate anion firstly. Then, the intermediate obtained was hydrolyzed into Zr−OH/‐OH 2 (Figure b) …”
Section: Resultsmentioning
confidence: 99%
“…During this process, possibly EtOH/EtO − pairs replaced formate anion firstly. Then, the intermediate obtained was hydrolyzed into Zr−OH/‐OH 2 (Figure b) …”
Section: Resultsmentioning
confidence: 99%
“…In the presence of sodium formate, ZIF‐8 initially grows through nanoparticle aggregation, before transitioning to a linker‐particle attachment . We hypothesize that this growth mode results in defects in the core of the large crystals and that linker exchange initially occurs at these defect sites, as suggested by theoretical calculations for ZIFs and experimentally observed in other MOFs . The resulting local changes in pore polarity and hydrogen bonding capability likely favor the adsorption and incorporation of further CHO‐HIm molecules.…”
Section: Figurementioning
confidence: 61%
“…For instance, phosphate or acetate buffers that are frequently used electrolytes have been known to cause framework collapse in multiple carboxylate-based frameworks [46]. In an illuminating study, Marreiros et al found that prolonged exposure of UiO-66 to methanol generates missing-linker defects, equilibrating at approximately one missing linker per unit cell [47]. While this does not necessarily lead to framework collapse, the defect makeup and porosity may be altered in an unpredictable way.…”
Section: Solvent and Coordinating Substancesmentioning
confidence: 99%